The role of urban habitats in the abundance of red squirrels (Sciurus vulgaris, L.) in Finland - Jokimäki, Jukka; Selonen, Vesa; Lehikoinen, Aleksi; Kaisanlahti-Jokimäki, Marja-Liisa (Urban Forestry & Urban Greening, 2019)
Because the amount of urban areas has increased, it is important to investigate the abundance of wildlife species in relation to urban environments. Analyzing the impact of urbanization on the presence of forest-dwelling mammals is of interest due to the possible effects of urbanization on human-wildlife relationships and urban biodiversity. The Eurasian red squirrel (Sciurus vulgaris) is a declining forest species, and its occurrence in urban environments has been inadequately studied. The loss and fragmentation of forests due to urbanization may be detrimental for squirrels, whereas the abundant and predictable food resources and the low number of natural predators in urban areas may encourage squirrels to invade towns. We used large-scale data collected by volunteer bird watchers along a 950 km south-north gradient to study whether the winter abundance of squirrels in Finland is dependent on urbanization, while controlling for effects of habitat type, food abundance (spruce cone crop; number of winter feeding sites), predator abundance (northern goshawk, Accipiter gentilis; feral cat Felis catus), season and latitude. We found that squirrel abundance increased with human population density, number of feeding sites and spruce cone crop and decreased with latitude and season. Feral cats showed weak negative connection with squirrel numbers, but there were no effect of goshawks. Relative squirrel abundance was approximately twice as high in urban habitats than in forests. Artificial feeding rather than a low number of predators may attract squirrels in urban environments. Planting spruce trees in urban environments will also benefit squirrels. Our results indicate that urban areas are an important habitat for the red squirrel even along the northern edge of their distribution range, where natural forest areas are still widespread. We conclude also that a citizen science - based bird survey protocol associated with mammal surveys seems to be a good large-scale monitoring method to study the urbanization of ...